Reactive arthritis in tuberculosis : a case of Poncet's disease - Ismail, Irmi Zarina; Ahmad, Zaiton; Hassan, Faezah (Academy of Family Physicians of Malaysia, 2013)
Reactive arthritis and erythema are uncommon presentations of tuberculosis (TB). Reactive arthritis in tuberculosis (TB) is known as Poncet's disease, a rare aseptic form of arthritis observed in patients with active TB. We report a case of Poncet's disease in a 20-year old man whose reactive arthritis overshadowed other clinical symptoms of TB resulting in delayed diagnosis and treatment. Although a conclusive diagnosis of Poncet's disease is not possible, reactive immunologic reactions such as reactive arthritis and erythema nodosum even without respiratory symptoms should raise suspicion on possible TB. Thus, taking a thorough medical history as well as performing relevant examinations and investigations for possible TB will help expedite the diagnostic process.